2022
DOI: 10.3390/mi13081241
|View full text |Cite
|
Sign up to set email alerts
|

Review of Recent Progress on Advanced Photocathodes for Superconducting RF Guns

Abstract: As is well known, the quality of the photocathodes is essential for the stability and reliability of photoinjector operations. Especially for superconducting radio frequency photoinjectors (SRF guns), the photocathode represents one of the most critical parts. Benefiting from the fast development of photocathode technology in recent years, several SRF guns have been successfully operated or tested for beam generation at the kHz–MHz repetition rate. In this paper, we will review the achievements as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Cesium telluride and Multi-alkali antimonide cathodes have already demonstrated their capability of operating at high duty-cycle regimes with the required charge, QE, and QE lifetimes [42][43][44]. Detailed reviews of cathode materials and of their properties can be found elsewhere [45][46][47].…”
Section: Photocathodes and Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cesium telluride and Multi-alkali antimonide cathodes have already demonstrated their capability of operating at high duty-cycle regimes with the required charge, QE, and QE lifetimes [42][43][44]. Detailed reviews of cathode materials and of their properties can be found elsewhere [45][46][47].…”
Section: Photocathodes and Lasersmentioning
confidence: 99%
“…Encouraging initial results from an R&D dedicated to the deposition of a layer of lead (a superconductor below 7.2 K) on niobium have demonstrated QE emissions of ~10 −3 that would allow operation at 100 kHz-class repetition rates [66]. The R&D effort now continues and focuses on improving the process reproducibility, the optimization of the surface roughness, and the characterization of the cathode intrinsic emittance and QE lifetime [47].…”
Section: Superconducting Rf Gunsmentioning
confidence: 99%
“…When used as a photocathode, the cesiated p-GaN can reach high quantum efficiency (QE) values of up to 70% [6][7][8] . The requirements for photocathodes for particle accelerator applications represent an extraordinary challenge with high expectations, for instance, a long lifetime, low thermal emittance, a fast response time, and high QE [9][10][11] . Recently, p-GaN has become increasingly popular as a potential electron source because it can be more robust than other semiconductor photocathodes.…”
mentioning
confidence: 99%